The data atlas of South Korea : demography, society, economic activity - Schwekendiek, Daniel J. (Jimoondang, 2014)
The Data Atlas of South Korea maps the demographic, social, and economic states of the southern half of the Korean peninsula by drawing upon the most recent census (2010) of the South Korean population. Although the focus of the book is on South Korea, it also utilizes corresponding census data from North Korea (reference year of 2008) in order to offer some comparative demographic perspectives of a unified peninsula. As such, the data atlas serves as a useful and unique reference book for readers interested in South Korea as well as Korean reunification.